Kerasukan sebagai Manifestasi Luka Batin: Sebuah Telaah Pastoral-Psikologis tentang Kerentanan Spiritual di Jemaat GMIM Elim Papakelan - Leyden Waljufri, Deni; Poluan, Agnes Relly (AISTHETIKOS Jurnal Ilmu Teologi dan Seni, 2026)
This qualitative case study analyzes the correlation between inner wounds (trauma) and the phenomenon of recurrent possession in the GMIM Elim Papakelan congregation. Possession treated solely by ritual deliverance often recurs. Findings indicate that pathological possession is an extreme manifestation of psychological stress due to inner wounds, which create a primary spiritual vulnerability gap and trigger extreme dissociation (consistent with DTD/Dissociative Theory: Spiegel et al., 2013). Empirical data (Case of Mother LR) demonstrates the failure of deliverance intervention without addressing the inner wound. Collective fear is identified as a secondary trigger. The study concludes that case management requires an Integrative Pastoral Counseling Model mandating Inner Healing rooted in Reformed theology of forgiveness to restore the subject's wholeness and permanently close the vulnerability gap. This model also corrects the erroneous monosemantic view that solely scapegoats the devil for psychological issues.